2019
DOI: 10.3126/jdean.v3i1.24060
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Illness Study of Regular Out Patient Department Diabetic in a Low Income Country: A Cross Sectional Study

Abstract: Background: The burden of Diabetes in South Asia is alarming as the prevalence is higher compared to other region, living cost is low after Sub Saharan Africa and health care system are in state of expanding to be more accessible and adequate.   Objectives: The objective of the study was to assess the direct cost of illness among diabetic patient regularly visiting at outpatient department (OPD) in BPKIHS. Methods: This was a cross sectional study done in year 2018.  142 patients with at least nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…26 This review also reported a cost per visit of US $4.39, laboratory cost of US $31.70 per year, and medicine cost of US $77.70 per year in Nepal in 2019. Among the limited cost of T2D studies in Nepal, Kattel et al 27 estimated that the average cost for medication and screening of diabetes was US $103 per year, and the mean indirect cost was US $102 per year. However, these estimates are different from those reported in the current study, because the study by Kattel et al reported the cost based on annual resource use in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…26 This review also reported a cost per visit of US $4.39, laboratory cost of US $31.70 per year, and medicine cost of US $77.70 per year in Nepal in 2019. Among the limited cost of T2D studies in Nepal, Kattel et al 27 estimated that the average cost for medication and screening of diabetes was US $103 per year, and the mean indirect cost was US $102 per year. However, these estimates are different from those reported in the current study, because the study by Kattel et al reported the cost based on annual resource use in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the current study, it was observed that the productivity loss of the patient was mostly accounted for by indirect cost. However, it was observed in the published literature that absenteeism, presenteeism, and premature mortality significantly contributed to indirect cost [34][35][36]. In addition, it was also noted that food and travel significantly contributed to the indirect cost [35].…”
Section: Discussionmentioning
confidence: 99%
“…A gradual increase in publications was observed in the years 2015–2017. (Afroz et al, 2019 ; Akari et al, 2013 ; Andersson et al, 2020 ; Anja & Laura, 2017 ; Anja & Laura, 2017 ; Bommer et al, 2017 ; Bommer et al, 2018 ; Boyanov et al, 2011 ; Bruno et al, 2012 ; Chatterjee et al, 2011 ; Chow et al, 2018 ; Elgart et al, 2014 ; Erzse et al, 2019 ; Hex et al, 2012 ; Hussain et al, 2014 ; Ibrahim, 2014 ; Javanbakht et al, 2011 ; Karachaliou et al, 2014 ; Kattel et al, 2019 ; Khan et al, 2020 ; Köster et al, 2011 ; Köster et al, 2011 ; Lesniowska & Skrzekowska-Baran, 2011 ; Leśniowska et al, 2014 ; Marcellusi et al, 2016 ; Mokdad et al, 2015 ; Palmer et al, 2012 ; Quaye et al, 2011 ; Riewpaiboon et al, 2011 ; Sortsoe et al, 2016 ; Suleiman & Festus, 2015 ; Todorova et al, 2012 ; Ulrich et al, 2016 ; Ying et al, 2011 ; Zhuo et al, 2014 ). Further details can be seen in Figure 2 .…”
Section: Preview Of the Proceduresunclassified